2016
DOI: 10.1002/mnfr.201600186
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pectin on fermentation characteristics, carbohydrate utilization, and microbial community composition in the gastrointestinal tract of weaning pigs

Abstract: The LMP, HMP, and aSBM, differently affected the digestion processes compared to the control diet and shaped the colonic microbiota from a Lactobacillus-dominating flora to a Prevotella-dominating community, with potential health-promoting effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(91 citation statements)
references
References 35 publications
(54 reference statements)
6
71
1
1
Order By: Relevance
“…A good gut microbiota is able to benefit the host by regulating physiological process and mucosal immunity such as suppressing proliferation of enteric pathogens [20], strengthening integrity of intestinal barrier on epithelial cells [21,22] and producing antimicrobial peptides in mucus layer [23]. In this study, Bacteroides and Firmicutes were the two dominant phyla, and Prevotella was the dominant bacterial species at the genus level, corresponding with the previous studies in which the most abundant phyla detected in the fecal samples of weaned piglets were Firmicutes and Bacteroides [24][25][26][27]. This research showed that Firmicutes abundance was increased in the CPB group but decreased in the antibiotic group.…”
Section: Discussionsupporting
confidence: 85%
“…A good gut microbiota is able to benefit the host by regulating physiological process and mucosal immunity such as suppressing proliferation of enteric pathogens [20], strengthening integrity of intestinal barrier on epithelial cells [21,22] and producing antimicrobial peptides in mucus layer [23]. In this study, Bacteroides and Firmicutes were the two dominant phyla, and Prevotella was the dominant bacterial species at the genus level, corresponding with the previous studies in which the most abundant phyla detected in the fecal samples of weaned piglets were Firmicutes and Bacteroides [24][25][26][27]. This research showed that Firmicutes abundance was increased in the CPB group but decreased in the antibiotic group.…”
Section: Discussionsupporting
confidence: 85%
“…The concentrations of SCFA, including acetate, propionate and butyrate in intestinal tract increased in varying degrees after extra addition of slowly digested carbohydrates in daily diets, such as resistant starch, 39) guar gum, 40) pectin, 41) inulin 42) and so on. In this study, acarbose and voglibose significantly increased butyrate concentration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The most familiar and predominant structural element in pectin is formed by the “smooth” homogalacturonan regions and is composed predominantly of a homopolymer of partially methyl esterified (1–4)-linked α- d -galacturonic acid (GalA) units [12]. The health benefits of pectin might include alterations in the composition of intestinal microbiota and the production of short-chain fatty acids [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Cui et al [10] reported that Bifidobacteria intake could play a role in the remission of ulcerative colitis (UC) and that prebiotics, such as dietary fiber, are ingredients in food that may increase the functions of probiotics in the human body. Previous research has suggested that a sufficient intake of dietary fiber with prebiotic effects is necessary for patients with chronic constipation [11,12,13]. Pectin, one typical kind of dietary fiber, is usually present in the cell walls of fruits, vegetables, and legumes [14].…”
Section: Introductionmentioning
confidence: 99%